1996
DOI: 10.1006/viro.1996.0047
|View full text |Cite
|
Sign up to set email alerts
|

Beet Soil-Borne Virus RNA 3—A Further Example of the Heterogeneity of the Gene Content of Furovirus Genomes and of Triple Gene Block-Carrying RNAs

Abstract: The complete nucleotide sequence of RNA 3 of the Ahlum isolate of beet soil-borne virus (BSBV) was determined from cDNAs obtained with immunocaptured virus particles and denatured preparations of dsRNA. BSBV RNA 3 is unique among the plant virus RNAs studied so far in containing apparently only the coding sequences of a triple gene block (TGB). The derived amino acid sequences of the three putative TGB-encoded proteins showed the highest level of sequence similarities with those of the corresponding proteins o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…The CP ORF has an opal translational termination codon and readthrough of this codon produces a large 84 kDa polypeptide (Hsu & Brakke, 1985). The CP readthrough domain (RT) is required for plasmodiophorid transmission of the virus (Koenig et al, 1997;Tamada & Kusume, 1991). The 39-proximal ORF of RNA2 encodes a 19 kDa polypeptide and its function is also not known.…”
Section: Introductionmentioning
confidence: 99%
“…The CP ORF has an opal translational termination codon and readthrough of this codon produces a large 84 kDa polypeptide (Hsu & Brakke, 1985). The CP readthrough domain (RT) is required for plasmodiophorid transmission of the virus (Koenig et al, 1997;Tamada & Kusume, 1991). The 39-proximal ORF of RNA2 encodes a 19 kDa polypeptide and its function is also not known.…”
Section: Introductionmentioning
confidence: 99%
“…Originally reported in Italy (Canova, 1959), rhizomania disease is now widespread in most countries where sugar beet is grown (McGrann et al, 2009) and BSBV is often found in beet infected with BNYVV (Meunier et al, 2003). However, the pathogenicity of BSBV and its contribution to the rhizomania syndrome remain unclear, with opinions still divided on this (Prillwitz & Schlösser, 1992;Kaufmann et al, 1993;Lindsten, 1993;Rush & Heidel, 1995).The BSBV genome consists of three single-stranded RNAs of positive polarity, packaged into rod-shaped particles (Koenig et al, 1996(Koenig et al, , 1997Koenig & Loss, 1997). RNA-1 (5.8 kb) encodes the putative viral replicase.…”
mentioning
confidence: 99%
“…The BSBV genome consists of three single-stranded RNAs of positive polarity, packaged into rod-shaped particles (Koenig et al, 1996(Koenig et al, , 1997Koenig & Loss, 1997). RNA-1 (5.8 kb) encodes the putative viral replicase.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Natural variation in RNA length has been reported with BSBV (19), and genomic deletions in soilborne wheat mosaic virus, the type member of the genus Furovirus, can be caused by variations in air and/or soil temperatures at the time of sample collection (37). Because variation is common among members of the genus Furovirus, it is not surprising that we detected variation in the number and size of BSBMV RNA species.…”
Section: Discussionmentioning
confidence: 65%